Step-by-step explanation:
multiply the first equation by 1, the second by -1 and add.
x + 2y = -16
-x - 6y = 28
--------------------
0 - 4y = 12
-4y = 12
y = -3
x + 2×-3 = -16
x - 6 = -16
x = -10
The relevant formula that we can use in this situation is:
v = v0 + at
where v is the final velocity, v0 is the initial velocity
= 20 km/hr, a is acceleration at 3.4 m/s^2 and t is time at 20 seconds
First convert v0 to m/s, v0 = 5.56 m/s
v = 5.56 m/s + 3.4 m/s^2 * 20 s
v = 73.56 m/s
Then convert back to km/hr:
<span>v = 264.82 km/hr</span>
Okay add 78 and 66. Then add 96 and 108. It should be 144 by 204. I know math is hard, but when you work at it you can do amazing things! I hope that helps you.